2013
DOI: 10.3153/jfscom.2013040
|View full text |Cite
|
Sign up to set email alerts
|

FOOD AND FEEDING HABIT OF SPINY EEL Macrognathus aral (Bloch and Schneider) FROM UPPER ASSAM

Abstract: Food and feeding habits of for M. aral were studied by examining a total of 421 digestive tracts during August, 2008 and July, 2010. It is very important to know the feeding habits of the fish in the natural environment in order to conduct stock enhancement by releasing the seedlings, because prevention of starvation, improvements of their growth and effective management can be conducted from this knowledge. The results reveals that the lowest value of relative length of gut (RLG) was found as 0.58(±0.09) in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…The RLG appears to decrease with increase in body length in R. daniconius (Wijegoonawardana, 1990), and it does not seem to change much with increase in body length in D. aequipinnatus and B. sarana (Wijegoonawardana, 1990). Parameswaran et al (1970) and Abujam et al (2013Abujam et al ( & 2014) found that the food and feeding habits changes as they grow into adult of N. nandus and spiny eels. Interestingly, this variation was noticed in both young and adult fish, thus ruling out any substantial change in diet.…”
Section: Size Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…The RLG appears to decrease with increase in body length in R. daniconius (Wijegoonawardana, 1990), and it does not seem to change much with increase in body length in D. aequipinnatus and B. sarana (Wijegoonawardana, 1990). Parameswaran et al (1970) and Abujam et al (2013Abujam et al ( & 2014) found that the food and feeding habits changes as they grow into adult of N. nandus and spiny eels. Interestingly, this variation was noticed in both young and adult fish, thus ruling out any substantial change in diet.…”
Section: Size Groupmentioning
confidence: 99%
“…The occurrence of low feeding in other fishes coincide with their peak breeding was reported by several workers (Fatima andKhan, 1993 andSerajuddin et al 1988). The high feeding intensity in spiny eel (M. pancalus & M. aral) was recorded in early maturity and was relatively lower in ripening of the gonad (Abujam et al, 2013(Abujam et al, & 2014.…”
Section: Size Groupmentioning
confidence: 99%
“…Among the examined species, E. danrica, P. sophore and X. cancila were found to be highest feeding intensity. Generally, feeding intensity is invariably more in pre-monsoon and monsoon while it was decline from post monsoon onwards (Abujam et al, 2013.…”
Section: Dibya Jyoti Deori Et Al 11(3): 043-047 (2017)mentioning
confidence: 99%
“…(1976) as the fish grow in length there will be a change in food habits from the carnivores to herbivores through omnivorous type and it was also incorporated by Abujam et al (2013.…”
Section: Dibya Jyoti Deori Et Al 11(3): 043-047 (2017)mentioning
confidence: 99%
See 1 more Smart Citation